A rare case of primary parasitic leiomyoma - S, Sreelatha; Kumar, Ashok; Nayak, Vedavathy; Punneshetty, Sahana; Hanji, Nirmala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
We report a rare case of a parasitic fibroid in a 42 year old woman who presented with mass per abdomen and backache. Ultrasound showed a mass suggestive of posterior wall fibroid. Laparotomy revealed a parasitic fibroid densely adherent to the omentum and extending retroperitoneally. Histopathological findings were consistent with leiomyoma.